Surface controls on the characteristics of natural CO2 seeps: implications for engineered CO2 stores. Issue 3 (19th November 2014) - Roberts, J. J.; Wood, R. A.; Wilkinson, M.; Haszeldine, S.
Abstract CO2 injected into rock formations for deep geological storage must not leak to surface, since this would be economically and environmentally unfavourable, and could present a human health hazard. In Italy natural CO2 degassing to the surface via seeps is widespread, providing an insight into the various styles of subsurface 'plumbing' as well as surface expression of CO2 fluids. Here we investigate surface controls on the distribution of CO2 seep characteristics (type, flux and temperature) using a large geographical and historical data set. When the locations of documented seeps are compared to a synthetic statistically random data set, we find that the nature of the CO2 seeps is most strongly governed by the flow properties of the outcropping rocks, and local topography. Where low‐permeability rocks outcrop, numerous dry seeps occur and have a range of fluxes. Aqueous fluid flow will be limited in these low‐permeability rocks, and so relative permeability effects may enable preferential CO2 flow. CO2vents typically occur along faults in rocks that are located above the water table or are low permeability. Diffuse seeps develop where CO2 (laterally supplied by these faults) emerges from the vadose zone and where CO2 degassing from groundwater follows a different flow path due to flow differences for water and CO2 gas. Bubbling water seeps (characterized by water bubbling with CO2) arise where CO2 supply enters the phreatic zone or an aquifer. CO2‐rich springs often emerge where valleys erode into CO2 aquifers, and these are typically high flux seeps. Seep type is known to influence human health risk at CO2 seeps in Italy, as well as the topography surrounding the seep which affects the rate of gas dispersion by wind. Identifying the physical controls on potential seep locations and seep type above engineered CO2 storage operations is therefore crucial to targeted site monitoring strategy and risk assessment. The surface geology and topography above a CO2 store must therefore be characterized in order to design the most effective monitoring strategy.